Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Chapter 5 - Trigonometric Identities - Section 5.4 Sum and Difference Identities for Sine and Tangent - 5.4 Exercises - Page 227: 53


(a) $$\sin(s+t)=\frac{77}{85}$$ (b) $$\tan(s+t)=-\frac{77}{36}$$ (c) $(s+t)$ lies in quadrant II.

Work Step by Step

To find $\sin(s+t)$ and $\tan(s+t)$, all values of $\sin s$, $\sin t$, $\cos s$, $\cos t$, $\tan s$ and $\tan t$ must be known. Therefore, the privileged job is to find all 6 essential values of $\sin s$, $\sin t$, $\cos s$, $\cos t$, $\tan s$ and $\tan t$. $$\cos s=-\frac{8}{17}\hspace{1.5cm}\cos t=-\frac{3}{5}\hspace{1.5cm}\text{s and t in quadrant III}$$ 1) Find $\sin s$, $\sin t$, $\cos s$, $\cos t$, $\tan s$ and $\tan t$. $s$ and $t$ are in quadrant III, so $\sin t\lt0$, $\cos t\lt0$, $\sin s\lt0$ and $\cos s\lt0$; but $\tan t=\frac{\sin t}{\cos t}\gt0$ and $\tan s=\frac{\sin s}{\cos s}\gt0$ $\sin^2 s=1-\cos^2 s=1-\Big(-\frac{8}{17}\Big)^2=1-\frac{64}{289}=\frac{225}{289}$ $\sin s=-\frac{15}{17}$ $\sin^2 t=1-\cos^2t=1-\Big(-\frac{3}{5}\Big)^2=1-\frac{9}{25}=\frac{16}{25}$ $\sin t=-\frac{4}{5}$ $$\tan s=\frac{\sin s}{\cos s}=\frac{-\frac{15}{17}}{-\frac{8}{17}}=\frac{15}{8}$$ $$\tan t=\frac{\sin t}{\cos t}=\frac{-\frac{4}{5}}{-\frac{3}{5}}=\frac{4}{3}$$ (a) Find $\sin(s+t)$ $$\sin(s+t)=\sin s\cos t+\cos s\sin t\hspace{1.5cm}\text{(sine sum identity)}$$ $$\sin(s+t)=\Big(-\frac{15}{17}\Big)\times\Big(-\frac{3}{5}\Big)+\Big(-\frac{8}{17}\Big)\times\Big(-\frac{4}{5}\Big)$$ $$\sin(s+t)=\frac{45}{85}+\frac{32}{85}$$ $$\sin(s+t)=\frac{77}{85}$$ (b) Find $\tan(s+t)$ $$\tan(s+t)=\frac{\tan s+\tan t}{1-\tan s\tan t}\hspace{1.5cm}\text{(tangent sum identity)}$$ $$\tan(s+t)=\frac{\frac{15}{8}+\frac{4}{3}}{1-\frac{15}{8}\times\frac{4}{3}}$$ $$\tan(s+t)=\frac{\frac{77}{24}}{1-\frac{5}{2}}$$ $$\tan(s+t)=\frac{\frac{77}{24}}{-\frac{3}{2}}=-\frac{77\times2}{24\times3}$$ $$\tan(s+t)=-\frac{77}{36}$$ (c) We see that $\sin(s+t)\gt0$ and $\tan (s+t)\lt0$. $\tan (s+t)=\frac{\sin(s+t)}{\cos(s+t)}$, this means $\cos(s+t)\lt0$ $\sin(s+t)\gt0$ but $\cos(s+t)\lt0$ show that $(s+t)$ lies in quadrant II.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.